Penguatan Pendidikan Moral Berbasis Karakter - Gea, Agus Putra; Hulu, Arya Willfred Ebenzer; Harefa, Noveri Amal Jaya; Hulu, Rikardo Number Wandis; Zebua, Vemky The Better (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Character education has been carried out since ancient times, but in the long run it will be eroded by modernization and modernization is often lost. This condition is suspected to have originated from the growth of verbalistic culture from the learning process which tends to be limited to textual moral education. This attraction aims to find out the strengthening of character-based moral education. The type of research used is a qualitative approach with a descriptive method. The subjects of the study were children, adolescents and young people who were exposed to the purposive sampling technique. Data collection techniques consist of observation, interviews, and documentation. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The findings of this study, namely education to form morals (moral education), or education to develop character (character education), in the current context are very relevant to overcome the moral crisis that is currently hitting the Unitary State of the Republic of Indonesia. Moral education is the cultivation, development, and formation of noble morals in a person. Moral education is a behavioral priority that must be implemented, fought, and habituated to by a person from childhood to adulthood. Character education is a form of human activity in which there are actions that educate and are intended for the next generation